Biallelic Mutations in P4HTM Cause Syndromic Obesity - Saeed, Sadia; Ning, Lijiao; Badreddine, Alaa; Mirza, Muhammad Usman; Boissel, Mathilde; Khanam, Roohia; Manzoor, Jaida; Janjua, Qasim M.; Khan, Waqas I.; Toussaint, Bénédicte; Vaillant, Emmanuel; Amanzougarene, Souhila; et al. (Diabetes (New York, N.Y.), 2023)
We previously demonstrated that 50% of children with obesity from consanguineous families from Pakistan carry pathogenic variants in known monogenic obesity genes. Here, we have discovered a novel monogenetic recessive form of severe childhood obesity using an in-house computational staged approach. The analysis included whole-exome sequencing data of 366 children with severe obesity, 1,000 individuals of the Pakistan Risk of Myocardial Infarction Study (PROMIS) study, and 200,000 participants of the UK Biobank to prioritize genes harboring rare homozygous variants with putative effect on human obesity. We identified five rare or novel homozygous missense mutations predicted deleterious in five consanguineous families in P4HTM encoding prolyl 4-hydroxylase transmembrane (P4H-TM). We further found two additional homozygous missense mutations in children with severe obesity of Indian and Moroccan origin. Molecular dynamics simulation suggested that these mutations destabilized the active conformation of the substrate binding domain. Most carriers also presented with hypotonia, cognitive impairment, and/or developmental delay. Three of the five probands died of pneumonia during the first 2 years of the follow-up. P4HTM deficiency is a novel form of syndromic obesity, affecting 1.5% of our children with obesity associated with high mortality. P4H-TM is a hypoxia-inducible factor that is necessary for survival and adaptation under oxygen deprivation, but the role of this pathway in energy homeostasis and obesity pathophysiology remains to be elucidated.